Effect of temperature and pressure on the interfacial morphology and bond strength of thermally laminated glycol-modified polyethylene terephthalate/styrene-co-butadiene block copolymer films and comparison with coextruded (polyethylene terephthalate/styrene-co-butadiene block copolymer/polyethylene terephthalate) and polyethylene terephthalate/styrene-co-butadiene block copolymer/polyethylene terephthalate films heated with applied pressure after extrusion. (April 2022) - Ishida, Katsunori; Nishitsuji, Shotaro; Miyata, Ken
This study focuses on controlling the interfacial adhesive strength between heat-sealed styrene-co-butadiene block copolymer (SBC) and glycol-modified polyethylene terephthalate (PETG) multilayer films. In comparison, the interfacial bond strength of coextruded PETG/SBC/PETG films was weaker. The lamella structures of SBC and free polybutadiene increased the interfacial adhesive strength. The coextruded films with applied thermal pressing were also examined. When exposed to heat, the interfacial adhesive strength improved. The butadiene layer segregated along the adhesive interface, as observed by transmission electron microscopy. The butadiene layer improved the interfacial adhesive strength. The applied pressure caused the butadiene layer to segregate in a parallel manner along the adhesive interface. The developed lamellar structure did not increase adhesive strength. We considered that the adhesive strength decreased due to a thinner butadiene layer with higher pressure. We concluded that adhesive segregation along the adhesive interface improved the bond strength.